The Analysis of the Risk Factors of Adverse Prognosis of Myocardial Infarction in the Acute Period - A. E. Zakharova; E. A. Spiridonova; N. F. Plavunov; Yu. V. Nikiforov; E. D. Avdeeva; M. B. Lagutin (Общая реаниматология)
The aim was to identify the risk factors contributed to adverse outcome of myocardial infarction (MI) in the acute period of the disease at a prehospital stage.Materials and methods. The study included the call cards of specialized resuscitation and anesthesia units of the budgetary institution A. S. Puchkov «Station of emergency medical care», to patients with complicated MI. The study included two groups of patients. The first group comprized of patients with complicated MI which resulted in circulatory arrest (n=184), the second group (the group of comparison) included patients with com plicated MI without the outcome in circulatory arrest (n=271). Statistical processing of the material: significance of differences between two binomial observations was evaluated by the Barnard's Exact Test.The results of the research. The presence of risk of MI complication as a stopping of blood circulation was confirmed in patients of the age group of 40—60 years (P=0.01). Patients with MI complicated by a circulatory arrest was characterized by a significantly greater intensity of pain syndrome (the pain intensity of 9—10 points was typ ical for 11,2% and 3% of patients of the group with circulatory arrest and the group of comparison, respectively; P< 0.001). The combination of clinical manifestations of alveolar pulmonary edema and arrhythmia occurred in 50% of patients with circulatory arrest, resulted in poor prognosis (the frequency of same parameters in a control group was 28,7%, P=0.018). Tachysystolic arrhythmia was the most common form of alteration at a circulatory arrest.Conclusions. The risk factors for MI adverse outcome in acute period included age from 40 to 60 years, pain of high intensity, presence of cardiogenic shock in combination with alveolar pulmonary edema and tachyarrhythmia.